Investigation of root canal morphologies of anterior and premolar teeth using cone beam computed tomography - Baybars, Sümeyye Coşgun; Yeler, Defne (My University, 2024)
Aim: The aim of this study is to examine the root canal morphology of anterior and premolar teeth in a group of Turkish population using cone beam computed tomography. Materials and Methods: Radiographic data of individuals who applied to Cumhuriyet University Faculty of Dentistry and had cone beam computed tomography for various reasons between 2015 and 2017 were evaluated retrospectively. A total of 3702 teeth were examined in terms of root numbers, root canal morphology and symmetry. Vertucci classification was used to determine root canal morphologies. Results: A total of 3702 mandibular and maxillary teeth of 400 patients, 185 males and 215 females, aged between 16-79 years (mean 35.2) were evaluated. The most common root canal shape in mandibular teeth was Vertucci Type I (62.0-89.3%). A high rate of Type III (32.2-32.4%) root canal shape was observed in mandibular incisors. Type I root canal shape was found most commonly (93.5 95.9%) in maxillary anterior teeth. While all of the two-rooted maxillary first premolars have a type I root canal shape in each root; Type IV root canal shape was the most common (79.4%) in single rooted maxillary first premolars. A high rate of Type I (41.6%) and then Type IV (23.3%) root canal shapes were seen in maxillary second premolars. The lowest symmetry rate was 85.0% in teeth numbered 31-41, and the highest symmetry rate was 96.2% which seen in teeth numbered 12-22 and 14-24. Symmetry rate was found to be lower in all mandibular teeth compared to maxillary teeth. Most of the maxillary first premolars (62%) have two roots and most of the other examined teeth (82.1 100%) had a single root. In maxillary and mandibular canine teeth, two roots were found in 1.8% and 4.9%, respectively; 100.0% single root was found in all central incisors. Conclusion: According to the literature, although the teeth groups have certain common features within themselves, it has been revealed that morphological differences can be found in various studies. In our study, it is aimed to contribute to these differences.
Keywords: Symmetry; Cone beam computed tomography; root canal morphology